Microbiome Shifts Associated With the Introduction of Wild Atlantic Horseshoe Crabs (Limulus polyphemus) Into a Touch-Tank Exhibit - Friel, Ariel D.; Neiswenter, Sean A.; Seymour, Cale O.; Bali, Lauren Rose; McNamara, Ginger; Leija, Fabian; Jewell, Jack; Hedlund, Brian P. (Frontiers in Microbiology, 2020)
The Atlantic horseshoe crab (Limulus polyphemus) is a common marine aquarium species and model organism for research. There is potential monetary and conservation value in developing a stable captive population of horseshoe crabs, however, one major impediment to achieving captivity is a lack of knowledge regarding captive diseases. We utilized 16S rRNA gene amplicon sequencing to track changes in the microbiomes of four body locations in three wild-caught (tracked over 14 months in captivity) and three tank-acclimated (>2 years in captivity) adult L. polyphemus in a touch tank at Shark Reef Aquarium at Mandalay Bay in Las Vegas, NV. The wild population hosted diverse and distinct microbiomes on the carapace (260 ± 96 amplicon sequence variants or ASVs), cloaca (345 ± 77 ASVs), gills (309 ± 36 ASVs), and oral cavity (359 ± 37 ASVs), which were dominated by classes Gammaproteobacteria, Bacteroidia, and Alphaproteobacteria. A rapid decline in richness across all body locations was observed within 1 month of captivity, with tank-acclimated (>2 years) animals having <5% of the initial microbiome richness and a nearly completely restructured microbial community. Tank-acclimated horseshoe crabs possessed distinct microbiomes that were highly uneven and low in species richness on the carapace (31 ± 7 ASVs), cloaca (53 ± 19 ASVs), gills (17 ± 2 ASVs), and oral cavity (31 ± 13 ASVs). The carapace, oral cavity, and gills of the tank-acclimated animals hosted abundant populations of Aeromonas (>60%) and Pseudomonas (>20%), both of which are known opportunistic pathogens of aquatic animals and can express chitinases, providing a plausible mechanism for the development of the carapace lesion pathology observed in this and other studies. The cloaca of the tank-acclimated animals was slightly more diverse than the other body locations with Aeromonas, Enterococcus, Shewanella, and Vagococcus dominating the community. These results provide an important baseline on the microbiomes of both wild and tank-acclimated horseshoe crabs and underscore the need to continue to investigate how native microbial populations may protect animals from pathogens.